Directional postcopulatory sexual selection is associated with female sperm storage in Trinidadian guppies. (1st August 2016) - Devigili, Alessandro; Di Nisio, Andrea; Grapputo, Alessandro; Pilastro, Andrea
Abstract: Female sperm storage (FSS) is taxonomically widespread and often associated with intense sperm competition, yet its consequences on postcopulatory sexual selection (PCSS) are poorly known. Theory predicts that FSS will reduce the strength of PCSS, because sperm characteristics favored before and after FSS may be traded‐off, and opportunities for nondirectional PCSS should increase. We explored these questions in the guppy ( Poecilia reticulata ), by allowing females to mate multiply and by comparing the paternity pattern in two successive broods. Contrary to predictions, the variance in male fertilization success increased after FSS, driven by a change in male paternity share across broods. This change was positively associated with sperm velocity (measured before FSS) but not with the duration of FSS, indirectly suggesting that faster sperm were better in entering female storage organs, rather than in persisting within them. Other male traits, such as male size and orange color, heterozygosity, and relatedness to the female, did not influence paternity after FSS. These results indicate that processes associated with FSS tend to reinforce the strength of PCSS in guppies, rather than weaken it. Further work is necessary to test whether this pattern changes in case of more prolonged FSS.